A novel Meloidogyne graminicola effector, MgMO237, interacts with multiple host defence‐related proteins to manipulate plant basal immunity and promote parasitism. (30th March 2018) - Chen, Jiansong; Hu, Lili; Sun, Longhua; Lin, Borong; Huang, Kun; Zhuo, Kan; Liao, Jinling
Summary: Plant‐parasitic nematodes can secrete effector proteins into the host tissue to facilitate their parasitism. In this study, we report a novel effector protein, MgMO237, from Meloidogyne graminicola, which is exclusively expressed within the dorsal oesophageal gland cell and markedly up‐regulated in parasitic third‐/fourth‐stage juveniles of M. graminicola . Transient expression of MgMO237 in protoplasts from rice roots showed that MgMO237 was localized in the cytoplasm and nucleus of the host cells. Rice plants overexpressing MgMO237 showed an increased susceptibility to M. graminicola . In contrast, rice plants expressing RNA interference vectors targeting MgMO237 showed an increased resistance to M. graminicola . In addition, yeast two‐hybrid and co‐immunoprecipitation assays showed that MgMO237 interacted specifically with three rice endogenous proteins, i.e. 1, 3‐β‐glucan synthase component (OsGSC), cysteine‐rich repeat secretory protein 55 (OsCRRSP55) and pathogenesis‐related BetvI family protein (OsBetvI), which are all related to host defences. Moreover, MgMO237 can suppress host defence responses, including the expression of host defence‐related genes, cell wall callose deposition and the burst of reactive oxygen species. These results demonstrate that the effector MgMO237 probably promotes the parasitism of M. graminicola by interacting with multiple host defence‐related proteins and suppressing plant basal immunity in the later parasitic stages of nematodes.